A nitroxide polymer grafted carbon nanotube electrosorption material and its preparation method and its application in treating perfluorinated compounds in water
By grafting the nitrogen oxide polymer in situ on the surface of multi-wall carbon nanotubes to form a chemical bond bridge structure, the problems of low durability and low utilization of active groups in water treatment are solved, and the adsorption capacity is significantly improved and service life enhance the adsorption performance of perfluoro compounds.
Patent Information
- Application Number
- CN202410317276.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-20
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-03-20
AI Technical Summary
The existing electro-adsorption electrodes have problems with low durability and low utilization of active groups in water treatment, resulting in a decrease in adsorption performance and insufficient adsorption capacity of pollutants.
By grafting oxynitride polymers in situ on the surface of multi-walled carbon nanotubes, forming a chemical bond bridge structure, improving the interaction force and stability between the polymer and carbon nanotubes, enhancing the dispersion and active groups in water Utilization.
It significantly improves the adsorption capacity and service life of the electro-adsorption electrode, extends the stability of the electrode and the effective utilization of active ingredients, and improves the adsorption performance of perfluorochemical compounds.
Smart Images

Figure CN117983191B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water pollution control and sewage treatment, and in particular to an electric adsorption material of nitrogen oxide polymer grafted with carbon nanotubes, a preparation method thereof and application thereof in water treatment. Background Art
[0002] In the field of water treatment, adsorption technology transfers pollutants from water to the surface of adsorbents through the interaction between pollutants in water and adsorbents to achieve water purification. Adsorption technology has shown great prospects in the treatment of low-concentration industrial wastewater due to its low energy consumption, high adsorption capacity and environmental protection characteristics. However, most adsorption materials have problems in regeneration. For example, the separation and regeneration costs of adsorbents for thermal regeneration and chemical regeneration are high, which can easily cause secondary pollution.
[0003] In the prior art, polymers are used as active ingredients in electrosorption electrodes and are usually physically mixed with multi-walled carbon nanotubes (MWCNTs) to exert their effects. The structure of the electrosorption electrode is complex and mainly consists of three key structural components: redox polymer, multi-walled carbon nanotubes and titanium mesh. In this composite structure, the redox polymer is a crucial component because it has adsorption properties, including functional groups such as amino (NH) and nitroxide radicals (NO•), which play a key role in the electrosorption process. Multi-walled carbon nanotubes serve as ideal carriers, providing redox polymers with high specific surface area and excellent electrical conductivity, effectively promoting the electrosorption reaction. Titanium mesh is a substrate used to load catalysts to form electrodes.
[0004] Renewable electrosorbents, represented by NOx polymers, can achieve pollutant adsorption and efficient regeneration under clean electrical energy control. However, highly renewable electrosorbents usually suffer from polymer shedding and capacity expansion problems, which affect the stability of the electrosorption electrode.
[0005] There are two main deficiencies in the existing process: (1) Low durability: The low durability of the electrosorption electrode stems from its current preparation method, namely physical mixing. In this way, there is a lack of interaction between the effective ingredients of the redox polymer and the multi-walled carbon nanotube carrier. Therefore, in actual wastewater treatment, especially in complex chemical environments, the polymer is prone to desorption and dissolution, resulting in a reduction in the effective ingredients of the electrosorbent, and ultimately a decrease in the adsorption performance of the electrode. (2) Low utilization of active groups: High molecular weight polymers may agglomerate in a physically mixed state. The higher the molecular weight, the easier it is to agglomerate. This makes it difficult for some free radicals to diffuse into the surrounding solution, making it impossible to effectively play the role of the active ingredients. This situation leads to a reduction in adsorption capacity, limiting the performance and efficiency of the electrosorption electrode. Summary of the invention
[0006] In order to improve the stability and electrical adsorption capacity of the electrode, the present invention discloses an electrical adsorption material of a nitrogen oxide polymer grafted with carbon nanotubes, a preparation method thereof, and an application thereof in water treatment. The present invention aims to improve the stability by in-situ grafting of nitrogen oxide polymers on the surface of multi-walled carbon nanotubes through bridging between the polymer and the multi-walled carbon nanotubes. This method also enhances the dispersibility of the polymer in water. Therefore, when applied to the electrical adsorption of pollutants in water, the adsorption capacity and service life of the electrode are significantly improved. The present invention improves the combination mode of the effective components of the polymer electrical adsorption electrode, changing from traditional physical mixing to chemical bond bridging, which brings multiple advantages.
[0007] The first object of the present invention is to provide a method for preparing an electro-absorption material of oxynitride polymer grafted carbon nanotubes, comprising the following steps:
[0008] (1) Providing acidified multi-walled carbon nanotubes;
[0009] (2) The acidified multi-walled carbon nanotubes, initiator and polymer monomer are mixed, dissolved in an organic solvent, degassed, heated to react, and a suspension is obtained, which is then dispersed in a second organic solvent, and then solid-liquid separation is performed to obtain a solid phase to obtain MWCNT-g-PTMPM;
[0010] (3) The obtained MWCNT-g-PTMPM is mixed with an oxidant solution to undergo an oxidation reaction, thereby obtaining the electro-adsorption material of the nitride-polymer grafted carbon nanotubes.
[0011] In one embodiment of the present invention, in step (1), the acidified multi-walled carbon nanotubes are prepared by the following method: multi-walled carbon nanotubes are reacted with a mixed acid solution.
[0012] In one embodiment of the present invention, the mixed acid comprises concentrated sulfuric acid and concentrated nitric acid, the concentration of the concentrated sulfuric acid is 70.0wt%-98.3wt%, the concentration of the concentrated nitric acid is 68wt%-98wt%, and the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 2-4:1;
[0013] Reaction conditions: reaction temperature 40-80°C, reaction time 5-10 h;
[0014] The method also includes drying the obtained acidified multi-walled carbon nanotubes at 50-70° C. until the water evaporates completely;
[0015] The mass ratio of the multi-walled carbon nanotubes to the volume of the mixed acid solution is 1:400-1:600 g / mL.
[0016] In one embodiment of the present invention, in step (2), the acidified multi-walled carbon nanotubes account for 5wt%-15wt% of the total mass of the acidified multi-walled carbon nanotubes and the polymer monomers;
[0017] The first organic solvent is selected from one or more of 1,4-dioxane, N,N-dimethylformamide, acetone, methanol, ethyl acetate, tetrahydrofuran, and dichloromethane;
[0018] The conditions of the heating reaction are as follows: the heating temperature is 60-65° C. and the heating time is 14-30 h.
[0019] In one embodiment of the present invention, in step (2), the polymer monomer is selected from 2,2,6,6-tetramethyl-4-piperidinyl methacrylate (TMPM);
[0020] The initiator is selected from one or more of azobisisobutyronitrile, benzoyl peroxide and benzoyl peroxide;
[0021] The concentration of the initiator is 3-4 mg / mL;
[0022] The second organic solvent is selected from one or more of n-hexane, ethanol, dimethylformamide and petroleum ether.
[0023] In one embodiment of the present invention, in step (3), the oxidant in the oxidant solution is selected from m-chlorobenzoic acid and / or hydrogen peroxide;
[0024] The solvent of the m-chlorobenzoic acid solution is tetrahydrofuran and / or dichloromethane;
[0025] The conditions of the oxidation reaction are: reaction temperature is -2°C to 2°C, and time is 55-65 min.
[0026] The second object of the present invention is to provide an electro-absorption material of oxynitride polymer grafted carbon nanotubes, which is obtained by the preparation method described in the first object.
[0027] The third object of the present invention is to provide an electro-adsorption electrode, comprising the electro-adsorption material of the oxynitride polymer grafted with carbon nanotubes.
[0028] The fourth object of the present invention is to provide the electrosorption material of the nitroxide polymer grafted carbon nanotubes and the application of the electrosorption electrode in treating perfluorinated compounds in water.
[0029] In one embodiment of the present invention, the perfluorinated compound comprises perfluorooctanoic acid (PFOA), perfluorooctane sulfonic acid (PFOS), perfluorobutyric acid (PFBA), perfluoroheptanoic acid (PFHpA) and perfluorononanoic acid (PFNA).
[0030] The mechanism of material synthesis:
[0031] The surface of multi-walled carbon nanotubes after acid treatment is rich in carboxyl groups and has bending strain. The carbon atoms in this state are most vulnerable to attack by free radicals. When the initiator azobisisobutyronitrile is added, it decomposes under heating conditions to produce free radicals. These free radicals will generate polymer chain structures on the attacked carbon atoms to obtain the final polymer.
[0032] Compared with the prior art, the invention is innovative in that the structure of the polymer electrosorption electrode is combined by chemical bonding. The electrosorption electrode prepared in the prior art is a nitrogen oxide polymer P (TMA 50 -co-TMPM 50 ) and multi-walled carbon nanotubes to make P(TMA 50 -co-TMPM 50 )-MWCNT mixture, while the present invention is to in-situ graft multi-walled carbon nanotubes on MWCNT to make chemically bonded MWNT-gP (TMA 50 -co-TMPM 50 ).
[0033] ① Improved combining method: In the conventional method, the redox polymer and the multi-walled carbon nanotubes are combined by physical mixing, while the present invention adopts a more advanced method to in-situ graft the redox polymer onto the multi-walled carbon nanotubes.
[0034] ② Improved stability of the carbon nanotube grafting method: This improvement brings about a more stable carbon nanotube grafting method, thereby improving the stability of the redox polymer as an electrosorption material.
[0035] ③ Improved utilization of active ingredients: Due to the in-situ grafting of redox polymers with multi-walled carbon nanotubes, the polymers in this grafted state have morphological advantages, including active groups such as amino and nitroxide free radicals on the polymers, which are more likely to adsorb trace ionizable organic pollutants in water, thereby improving the utilization of active ingredients on the electrosorption electrode.
[0036] The above technical solution of the present invention has the following beneficial effects compared with the prior art:
[0037] The present invention improves the combination mode of effective components of high molecular polymer electrosorption electrode from traditional physical mixing to chemical bond bridging, which brings multiple advantages:
[0038] Stable carbon nanotube grafting: The improved grafting method provides a more stable connection through chemical bond bridging, thereby enhancing the stability of the redox polymer as an electrosorption material. This helps to extend the service life of the electrode and improve its reliability.
[0039] Improve the electrosorption capacity: Since the redox polymer is grafted with multi-walled carbon nanotubes in situ, the polymer in this grafted state has morphological advantages and improves the utilization rate of active ingredients on the electrosorption electrode. Since there are abundant active groups such as amino groups and nitroxide radicals on the carbon nanotube-grafted PTMPM polymer, and the amino group has a good affinity for perfluorinated compounds, the amino group can interact with perfluorinated compounds through hydrophobic forces to adsorb pollutants from the water body. In addition, under the condition of applying positive charge to the adsorption electrode, electrostatic forces also contribute to the adsorption of perfluorinated compounds, so the resulting polymer can adsorb perfluorinated compounds very well.
[0040] The present invention adopts a method of acidifying multi-walled carbon nanotubes to produce bends and structural defects on their surfaces, thereby making them more susceptible to attack by active free radicals, providing ideal sites for the grafting of redox polymers. In the polymerization reaction of grafted monomers on multi-walled carbon nanotubes, these carbon defect sites become growth points of polymer chains. Therefore, a stable bond is formed between the polymer and the carbon nanotubes, ensuring that the active ingredients of the polymer can remain stable during the electrosorption and regeneration process, thereby avoiding the dissolution of the active material. In addition, the grafted polymer is not prone to agglomeration, and its chain structure is not tightly wrapped around the nanotubes, but extends into the surrounding medium, which helps to better interact with the electrolyte. These innovative improvements improve the stability and activity of the electrosorption electrode, thereby increasing the adsorption capacity, thereby significantly improving its performance and efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0042] Figure 1 is a synthetic flow chart of the material of the present invention;
[0043] Figure 2 This is a nuclear magnetic resonance hydrogen spectrum characterization diagram of the synthetic material obtained in Example 2 of the present invention;
[0044] Figure 3 is the thermogravimetric graph of the polymer materials obtained in Examples 1-3 of the present invention grafted with polymers of different masses;
[0045] Figure 4 This is a diagram showing the stability test results of the redox polymer electrosorption electrode of the present invention. DETAILED DESCRIPTION
[0046] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0047] The key technical point of the present invention is that it takes the electrosorption of pollutants in water as the starting point, uses polymers for the first time to electrosorb trace pollutants in water, and overcomes the influence of the complex chemical environment in water on the solubilization of polymers by grafting polymers. Compared with the simple physical mixing method, the adsorption capacity of the adsorbent for pollutants is also improved.
[0048] Embodiment 1:
[0049] In this embodiment, when the mass fraction of acidified multi-walled carbon nanotubes is 5%, the synthesized polymer is MWNT-gP (TMA 50 -co-TMPM 50 ) 5% .
[0050] The preparation of the redox-active polymer electrosorption electrode is divided into the following three steps: acid treatment of multi-walled carbon nanotubes, in-situ grafting of polymers on multi-walled carbon nanotubes by free radical polymerization, and oxidative modification of groups on the grafted polymers.
[0051] (1) Acid treatment of multi-walled carbon nanotubes
[0052] Weigh 1 g of unprocessed multi-walled carbon nanotubes and place them in a 500 mL round-bottom flask. Add 300 mL of a mixed acid solution of concentrated H2SO4 and concentrated HNO3 in a volume ratio of 3:1, and ultrasonically treat at 50°C for 12 hours. Then dilute the mixed solution with 500 mL of distilled water in a 1000 mL beaker, filter it after cooling to room temperature, and wash it with distilled water several times until it is neutral to remove excess acid. The black solid finally obtained is placed in a vacuum drying oven and dried at 60°C for 24 hours to obtain acidified multi-walled carbon nanotubes. The bending strain on the surface of multi-walled carbon nanotubes and the structural defects caused by acid treatment make the C=C bonds on it vulnerable to attack by active free radicals.
[0053] (2) In-situ grafting of polymers
[0054] Take 2 grams of acidified multi-walled carbon nanotubes and polymer monomer (methacrylate-2,2,6,6-tetramethyl-4-piperidinyl ester), of which the mass of acidified multi-walled carbon nanotubes accounts for 5%. Add the above mixed materials together with 100 mg of azobisisobutyronitrile into a 200 ml Shrek bottle, then dissolve in 25 ml of 1,4-dioxane, stir evenly, and continue stirring for 10 minutes. The solvent is degassed using the "freeze-pump-thaw" method. The specific steps of the degassing treatment are: first, use liquid nitrogen to freeze the solution into a solid state, then use a vacuum pump with a vacuum degree of 10 Pa to evacuate for 3 minutes, then turn off the vacuum system, pass inert gas nitrogen, and slowly heat and melt the solution. Repeat this operation three times to complete the degassing of the mixed solution. Subsequently, use a water bath to heat the degassed mixture to 65°C and keep it warm for 16 hours. The obtained solution was dissolved in 300 ml of n-hexane, and the black solid at the bottom was separated and dispersed into 50 ml of acetone with the assistance of sonication, and then filtered using a 0.22 μm polytetrafluoroethylene membrane. The dispersion process was repeated three times to completely remove the physically adsorbed poly (methacrylate-2,2,6,6-tetramethyl-4-piperidinyl ester). Finally, the filtered black solid was dried at 60 ° C for use and named MWCNT-g-PTMPM. 5% .
[0055] (3) Oxidative modification of polymers
[0056] 200 mg of MWNT-g-PTMPM obtained in step (2) 5% Dissolve in 30 mL tetrahydrofuran solution and stir evenly. Then cool the mixture in an ice bath, slowly add 104 mg of m-chlorobenzoic acid in tetrahydrofuran solution (15 ml), and stir for 1 h. Filter on a 0.22 μm PTFE membrane, wash with deionized water 3 times, and finally dry under reduced pressure to obtain the oxidized MWNT-g-PTMPM. 5% , named MWNT-gP (TMA 50 -co-TMPM 50 ) 5% The number in the lower right corner refers to the degree of oxidation, such as MWNT-gP (TMA 50 -co-TMPM 50 ) 5% The two 50s in the figure represent the oxidation degree of 50%, which is different from the original MWNT-g-PTMPM. 5% The ratio is calculated from the oxidant m-chlorobenzoic acid.
[0057] Embodiment 2:
[0058] In this example, when the mass fraction of acidified multi-walled carbon nanotubes is 10%, the synthesized polymer is MWNT-gP (TMA 50 -co-TMPM 50 ) 10% .
[0059] The preparation of the redox-active polymer electrosorption electrode is divided into the following three steps: acid treatment of multi-walled carbon nanotubes, in-situ grafting of polymers on multi-walled carbon nanotubes by free radical polymerization, and oxidative modification of groups on the grafted polymers.
[0060] (1) Acid treatment of multi-walled carbon nanotubes
[0061] Weigh 1 g of unprocessed multi-walled carbon nanotubes and place them in a 500 mL round-bottom flask. Add 300 mL of a mixed acid solution of concentrated H2SO4 and concentrated HNO3 in a volume ratio of 3:1. Ultrasonic treatment is performed at 50°C for 12 hours. Then, the mixed solution is diluted with 500 mL of distilled water in a 1000 mL beaker. After cooling to room temperature, the solution is filtered and washed with distilled water several times until it is neutral to remove excess acid. The resulting black solid is placed in a vacuum drying oven and dried at 60°C for 24 hours to obtain acidified multi-walled carbon nanotubes.
[0062] (2) In-situ grafting of polymers
[0063] Take 2 grams of the acidified multi-walled carbon nanotubes and polymer monomer (methacrylate-2,2,6,6-tetramethyl-4-piperidinyl ester) obtained in step (1), wherein the mass proportion of the acidified multi-walled carbon nanotubes is 10%. Add the above mixed materials together with 100 mg of azobisisobutyronitrile into a 200 ml Shrek bottle, and then dissolve in 25 ml of 1,4-dioxane, stir evenly, and continue stirring for 10 minutes. The solvent is degassed by the "freeze-pump-thaw" method. The specific steps of the degassing treatment are as follows: first, use liquid nitrogen to freeze the solution into a solid state, then use a vacuum pump with a vacuum degree of 10 Pa to evacuate for 3 minutes, then turn off the vacuum system, introduce inert gas nitrogen, and slowly heat and melt the solution. Repeat this operation three times to complete the degassing of the mixed solution. Subsequently, use a water bath to heat the degassed mixture to 65°C and keep it warm for 16 hours. The obtained solution was dissolved in 300 ml of n-hexane, and the black solid at the bottom was separated and dispersed into 50 ml of acetone with the assistance of sonication, and then filtered using a 0.22 μm polytetrafluoroethylene membrane. The dispersion process was repeated three times to completely remove the physically adsorbed poly (methacrylate-2,2,6,6-tetramethyl-4-piperidinyl ester). Finally, the filtered black solid was dried at 60 ° C for use and named MWCNT-g-PTMPM. 10% .
[0064] (3) Oxidative modification of polymers
[0065] 200 mg MWNT-g-PTMPM obtained in step (2) 10% Dissolve in 30 mL of tetrahydrofuran solution and stir evenly. Then cool the mixture in an ice bath, slowly add 104 mg of m-chlorobenzoic acid dissolved in tetrahydrofuran solution (15 mL), and stir for 1 h. Filter on a 0.22 μm PTFE membrane, wash with deionized water 3 times, and finally dry under reduced pressure to obtain the oxidized MWNT-g-PTMPM 10% , named MWNT-gP (TMA 50 -co-TMPM 50 ) 10%, and the obtained polymer material was characterized by structure. The results are shown in Figure 2 and Figure 3 ,Depend on Figure 2 It can be seen that ① polymers are formed by polymerization of monomers, and Figure 2 The chemical shifts of different H in the graph can correspond to the monomer structure of PTMPM. Combined with the molecular weight characterization of the monomers described in Table 1, it can be shown that the synthesized polymer is a high molecular weight polymer composed of TMPM as a monomer. ②Nuclear magnetic resonance characterization is to elute the residual polymer on the surface of the synthesized material with an organic solvent. According to the free radical polymerization process of the polymer, it can be seen that the residual polymer and the polymer grafted on the surface of MWCNT have the same molecular weight.
[0066] Embodiment 3:
[0067] In this embodiment, when the mass fraction of acidified multi-walled carbon nanotubes is 15%, the synthesized polymer is MWNT-gP (TMA 50 -co-TMPM 50 ) 15% .
[0068] The preparation of the redox-active polymer electrosorption electrode is divided into the following three steps: acid treatment of multi-walled carbon nanotubes, in-situ grafting of polymers on multi-walled carbon nanotubes by free radical polymerization, and oxidative modification of groups on the grafted polymers.
[0069] (1) Acid treatment of multi-walled carbon nanotubes
[0070] Weigh 1 g of unprocessed multi-walled carbon nanotubes and place them in a 500 mL round-bottom flask. Add 300 mL of a mixed acid solution of concentrated H2SO4 and concentrated HNO3 with a volume ratio of 3:1. Ultrasonic treatment is performed at 50°C for 12 hours. Then, the mixed solution is diluted with 500 mL of distilled water in a 1000 mL beaker. After cooling to room temperature, the mixture is filtered and washed with distilled water several times until it is neutral to remove excess acid. The black solid finally obtained is placed in a vacuum drying oven and dried at 60°C for 24 hours. Acidified multi-walled carbon nanotubes are obtained.
[0071] (2) In-situ grafting of polymers
[0072] Take 2 grams of acidified multi-walled carbon nanotubes and polymer monomer (methacrylate-2,2,6,6-tetramethyl-4-piperidinyl ester), of which the mass of acidified multi-walled carbon nanotubes accounts for 15%. Add the above mixed materials together with 100 mg of azobisisobutyronitrile into a 200 ml Shrek bottle, then dissolve in 25 ml of 1,4-dioxane, stir evenly, and continue stirring for 10 minutes. The solvent is degassed using the "freeze-pump-thaw" method. The specific steps of the degassing treatment are: first, use liquid nitrogen to freeze the solution into a solid state, then use a vacuum pump with a vacuum degree of 10 Pa to evacuate for 3 minutes, then turn off the vacuum system, pass inert gas nitrogen, and slowly heat and melt the solution. Repeat this operation three times to complete the degassing of the mixed solution. Subsequently, use a water bath to heat the degassed mixture to 65°C and keep it warm for 16 hours. The obtained solution was dissolved in 300 ml of n-hexane, and the black solid at the bottom was separated and dispersed into 50 ml of acetone with the assistance of sonication, and then filtered using a 0.22 μm polytetrafluoroethylene membrane. The dispersion process was repeated three times to completely remove the physically adsorbed poly (methacrylate-2,2,6,6-tetramethyl-4-piperidinyl ester). Finally, the filtered black solid was dried at 60 ° C for use and named MWCNT-g-PTMPM. 15% .
[0073] (3) Oxidative modification of polymers
[0074] 200 mg MWNT-g-PTMPM obtained in step (2) 15% Dissolve in 30 mL tetrahydrofuran solution and stir evenly. Then cool the mixture in an ice bath, slowly add 104 mg of m-chlorobenzoic acid in tetrahydrofuran solution (15 ml), and stir for 1 h. Filter on a 0.22 μm PTFE membrane, wash with deionized water 3 times, and finally dry under reduced pressure to obtain the oxidized MWNT-g-PTMPM. 15% , named MWNT-gP (TMA 50 -co-TMPM50 ) 15% .
[0075] Polymer characterization
[0076] The polymers synthesized in Examples 1-3 were characterized by GCP gel chromatography and thermogravimetric analysis. The results are shown in Tables 1 and Figure 3 .
[0077] Table 1 Related parameters of polymers synthesized at different carbon nanotube dosages in the raw materials
[0078]
[0079] It can be seen from Table 1 above that the substance synthesized by the present invention is a high molecular polymer (because its molecular weight is 48627-171445).
[0080] Depend on Figure 3 It can be seen that: since the polymer grafted on the MWCNT surface will show obvious weight loss between 200-400, the thermogravimetric diagram can determine that the polymer is indeed successfully loaded on the MWCNT surface, and combined with the previous GPC results, the grafting weight of the polymer can be analyzed and obtained, as shown in Table 1.
[0081] Test example: MWNT-gP (TMA 50 -co-TMPM 50 ) Polymers for electrosorption
[0082] The electroadsorbent MWNT-gP (TMA) synthesized in Example 2 50 -co-TMPM 50 ) 10% Used to absorb perfluorooctanoic acid (PFOA C8HF 15 O2), the specific steps are as follows:
[0083] Step 1: Preparation of electrosorption electrodes
[0084] 1. Cut the titanium mesh with a pore size of 30 mesh into a size of 1 cm × 2 cm.
[0085] 2. 160 mg of MWNT-gP (TMA 50 -co-TMPM 50 ) 10% Disperse in 10 mL of acetone and sonicate in ice water for 1 h.
[0086] 3. Immerse the titanium mesh in MWNT-gP (TMA 50 -co-TMPM 50 ) 10%The mixed solution was immersed for 3 seconds each time, and then dried at room temperature for 30 seconds. 50 -co-TMPM 50 ) 10% The loading amount was controlled at about 0.6 mg to obtain an electrosorption electrode.
[0087] Step 2: Electrosorbent absorbs perfluorinated compounds in water and releases them
[0088] 1. Use a three-electrode system, wherein the electrosorption electrode obtained in step 1 is the working electrode, the platinum electrode is the counter electrode, and the silver chloride electrode is the reference electrode.
[0089] 2. Before the electrosorption operation, the groups on the working electrode need to be activated for subsequent electrosorption. The working electrode was activated by cyclic voltammetry in 0.1 M NaClO4 in the range of 0 - 1.2 V (vs. Ag / AgCl) with a scan rate of 10 mV s -1 , cycle 4 times.
[0090] 3. In an electrolyte containing perfluorinated compounds, an adsorption test was carried out at a constant potential of -1 V (vs. Ag / AgCl). The experimental results are shown in the attached Figure 4 .
[0091] 4. In a solution containing only electrolyte, applying a potential of 1 V (vs. Ag / AgCl) to the adsorbed working electrode can release the pollutants from the working electrode and achieve regeneration of the electrosorbent.
[0092] The results of the electrosorption, regeneration and stability tests of polymer electrodes are as follows: Figure 4 As shown. Figure 4 It can be seen that the adsorbent prepared by the present invention has an adsorption capacity of 200-250 mg / g of PFOA, a perfluorinated pollutant, and the regeneration rate of the adsorbent after adsorption is about 50-60%. The obtained material can operate stably and still maintain a high adsorption activity after 10 cycles of adsorption and desorption.
[0093] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing an electro-adsorption material of oxynitride polymer grafted carbon nanotubes, characterized in that: The following steps are involved: (1) Providing acidified multi-walled carbon nanotubes; (2) mixing the acidified multi-walled carbon nanotubes, an initiator and a polymer monomer, dissolving them in a first organic solvent, degassing them, heating them for reaction, obtaining a suspension, and dispersing them in a second organic solvent, and then performing solid-liquid separation to obtain a solid phase to obtain MWCNT-g-PTMPM; the polymer monomer is selected from 2,2,6,6-tetramethyl-4-piperidinyl methacrylate; (3) Mixing the obtained MWCNT-g-PTMPM with an oxidant solution to undergo an oxidation reaction, thereby obtaining the electro-adsorption material of the nitroxide polymer grafted carbon nanotubes; the oxidation reaction temperature is -2°C to 2°C, and the oxidation reaction time is 55-65 min; the oxidant in the oxidant solution is selected from m-chlorobenzoic acid and / or hydrogen peroxide.
2. The preparation method according to claim 1, characterized in that: In step (1), the acidified multi-walled carbon nanotubes are prepared by the following method: multi-walled carbon nanotubes are reacted with a mixed acid solution.
3. The preparation method according to claim 2, characterized in that: The mixed acid comprises concentrated sulfuric acid and concentrated nitric acid, the concentration of the concentrated sulfuric acid is 70.0wt%-98.3wt%, the concentration of the concentrated nitric acid is 68wt%-98wt%, and the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 2-4:1; Reaction conditions: reaction temperature 40-80°C, reaction time 5-10 h; The method also includes drying the obtained acidified multi-walled carbon nanotubes at 50-70° C. until the water evaporates completely; The mass ratio of the multi-walled carbon nanotubes to the volume of the mixed acid solution is 1:400-1:600 g / mL.
4. The preparation method according to claim 1, characterized in that: In step (2), the acidified multi-walled carbon nanotubes account for 5wt%-15wt% of the total mass of the acidified multi-walled carbon nanotubes and the polymer monomers; The first organic solvent is selected from one or more of 1,4-dioxane, N,N-dimethylformamide, acetone, methanol, ethyl acetate, tetrahydrofuran, and dichloromethane; The conditions of the heating reaction are as follows: the heating temperature is 60° C.-65° C., and the heating time is 14 h-30 h.
5. The preparation method according to claim 1, characterized in that: In step (2), the initiator is selected from one or more of azobisisobutyronitrile, benzoyl peroxide and benzoyl peroxide; The concentration of the initiator is 3-4 mg / mL; The second organic solvent is selected from one or more of n-hexane, ethanol, dimethylformamide and petroleum ether.
6. The preparation method according to claim 1, characterized in that: In step (3), the solvent of the oxidant solution is tetrahydrofuran and / or dichloromethane.
7. An electro-adsorption material of oxynitride polymer grafted with carbon nanotubes, characterized in that: Obtained by the preparation method according to any one of claims 1 to 6.
8. An electrosorption electrode, characterized in that: An electrosorption material comprising the nitride oxide polymer grafted with carbon nanotubes as claimed in claim 7.
9. Use of the electrosorption material of oxynitride polymer grafted carbon nanotubes as claimed in claim 7 or the electrosorption electrode as claimed in claim 8 in treating perfluorinated compounds in water.
10. The use according to claim 9, characterized in that: The perfluorinated compounds include perfluorooctanoic acid, perfluorooctane sulfonic acid, perfluorobutyric acid, perfluoroheptanoic acid and perfluorononanoic acid.
Citation Information
Patent Citations
Multi-carboxyl polymer grafted water-soluble carbon nanometer tube and preparation method thereof
CN1546545A
Manufacture method of conducting polymer coated carbon nanotube and conducting polymer coated carbon nanotube thereby
KR1020090019303A